Analisis Persepsi Masyarakat Terhadap Komunikasi Kebijakan Menggunakan Topic Modelling (Kebijakan Protokol Kesehatan Covid-19 Dalam Penggunaan Masker) - Rochmawati, Wulan Hilmi; Ramantoko, Gadang; Nurhazizah, Eva (STIKOM Tunas Bangsa Pematangsiantar, 2022)
The application of health protocols has become a new habit in the Covid-19 pandemic, one of which is the use of masks. Presidential Instruction Number 6 of 2020 on August 4, 2020, has stipulated the obligation to use masks in Indonesia. This study aims to determine the topics formed on the Twitter network and public perceptions before and before the implementation of the Presidential Instruction. Tweet data with the hashtags “#gunakanmasker” and “#indonesiaterserah” were collected during the period from March 2 to November 30, 2020. The data was processed using the Topic Modeling method with Python software. The results show that the topics formed before the Presidential Instruction were